Leisure Habits in Hungary and Abroad - Szabó, Katalin; Hőnyi, Dorottya; Kinczel, Antonia; Tütünkov-Hrisztov, Jordán; Molnár, Anikó; Müller, Anetta (Acta Carolus Robertus, 2022)
In our article, we examined the travel habits of Hungarian tourists, their attitudes towards the Bulgarian destination and the popular Bulgarian destinations. Our primary research (N = 810) confirms the finding of the Bulgarian statistical office that, in addition to the coast, winter ski tourism is becoming increasingly popular with tourists. Hungarian travelers still focus on the summer season, so the popularity of the Bulgarian coastal destination is indisputable, but the growing number of Hungarian tourists in the winter months justifies the strengthening of mountain destinations.
Keywords: bulgarian tourist destination; travel habits